The importance of psychological development for Malaysian students in facing Vision 2020 - Amit, Noh; Mohd. Jaladin, Rafidah Aga (2006)
The purpose of this paper is to discuss the importance of psychological development for Malaysian students in facing Vision 2020. Firstly it introduces the students and scenario of development in Malaysia. Secondly it elaborates the psychological impacts of national and global development such as the impact of economics, social and political development on studentsâ€™ psychological development and well-being. Thirdly it discusses the importance of psychological development for students in preparing them for vision 2020. Fourthly it highlights the preparation for studentsâ€™ psychological development and its challenges to Malaysian Government. Lastly it suggests the ideas and approaches in preparing (overcoming) the students’ psychological development in facing the Vision 2020.